WATER BALANCE DENGAN METODE THORNTHWAITE-MATHER DI DAERAH ALIRAN SUNGAI (DAS) LOANO HULU KABUPATEN PURWOREJO - Hartono, Gunawan (Green Earth, 2012)
Presence of water on earth not all of them can be used by living beings, especially humans. Watershed Loano Hulu is one of the watershed located in Central Java province. Loano DAS has a function for the area underneath. For the study of water balance is necessary to know the potential of water in the watershed, thereby criticality index can be determined so that the water in the watershed can be determined for watershed management measures are to be maintained. The purpose of this study is to determine the Water Holding Capacity (WHC) at the sites and determine the Water Balance. The research was conducted in the Upper Basin Loano Purworejo in Central Java Province. The research activities carried out in June 2009. The method used in the implementation of this study using the Thornthwaite-Mather. Data obtained on the basis of data WHC soil texture and extensive vegetation cover or land use, but it also needs climate data. Based on the results of the calculation results obtained WHC Loano watershed upstream of 245 mm. The size of the WHC reflects both the poor condition of a watershed. If the WHC of the watershed condition is very good, because it can save large amounts of water. Conversely the small WHC watershed condition is not good then it means the ability to store water is a small watershed. WHC value ofÂ  245 mm for the watershed Loano Hulu reflect the ability of the watershed to store water is high enough, so that the watershed is included in the DAS good condition. In meteorological amount of rainfall that occurred in the Upper Basin Loano big enough in January to reach 400 mm, the amount of rain up in June is still able to compensate for potential evapotranspiration occurs. Water deficit occurred during the five months from June to October occurred. Evapotranspiration that occurs less than the rainfall that occurred, so the watershed is a meteorologist had a surplus of water.Â Key words: soil, landuse, water holding capacity, water balance